2-Aminopyrimidine Derivatives as Potential Fluorescent Chemosensors for Trivalent Cations: Structural Characterization, Photophysical Properties, and Live-Cell Imaging - Gonzalez-Diaz, J (ELSEVIER, 2026)
Variations in metallic cation levels have been associated with chronic non-communicable diseases such as Alzheimer s and Parkinson s (e.g., Al(III) and Fe(III)) and diabetes (e.g., Cr(III)). In this context, fluorescent chemosensors are valuable tools for detecting cation concentrations in complex matrices. Herein, we report the synthesis of two fluorescent pyrimidines: 4-(4-(dimethylamino)phenyl)-6-phenylpyrimidin-2-amine (PY-H) and 4-(4-(dimethylamino)phenyl)-6-(4-fluorophenyl)pyrimidin-2-amine (PY-4F). The crystal structure of PY-4F reveals a 30.06 degrees torsion arrangement between the pyrimidine core and the -C6H4N(CH3)2 ring. Photophysical studies demonstrate selective fluorescence quenching in the presence of trivalent cations (Al(III), Cr(III), Fe(III)). Detection limits range from 0.060 to 0.570 mu M, all below the thresholds established for drinking water by international agencies such as the World Health Organization and Environmental Protection Agency. To elucidate the sensing mechanism, a computational study using DFT and TD-DFT methods was conducted. Cytotoxicity assays in SH-SY5Y cells revealed low toxicity, and successful cell labeling was achieved using epifluorescence and confocal microscopy. These results suggest that PY-H and PY-4F are promising fluorescent probes for detecting Al(III), Cr(III), and Fe(III) in cellular environments and potentially in other complex systems.
Keywords: 2-aminopyrimidine; Fluorescent Chemosensor; Metal ion detection; Trivalent cations; DFT calculations; SH-SY5Y cell imaging